2014
DOI: 10.1128/aem.01984-14
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Polymeric Substance Architecture Influences Natural Genetic Transformation of Acinetobacter baylyi in Biofilms

Abstract: Genetic exchange by natural transformation is an important mechanism of horizontal gene transfer in biofilms. Thirty-two biofilm metrics were quantified in a heavily encapsulated Acinetobacter baylyi strain and a miniencapsulated mutant strain, accounting for cellular architecture, extracellular polymeric substances (EPS) architecture, and their combined biofilm architecture. In general, transformation location, abundance, and frequency were more closely correlated to EPS architecture than to cellular or combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Merod and Wuertz 2014; Wang et al 2002) and was found to occur frequently, as biofilms are hotspots, i.e. offer ideal conditions for HGT including high cell density, increased genetic competence and an accumulation of exDNA.…”
Section: Biofilmsmentioning
confidence: 99%
“…Merod and Wuertz 2014; Wang et al 2002) and was found to occur frequently, as biofilms are hotspots, i.e. offer ideal conditions for HGT including high cell density, increased genetic competence and an accumulation of exDNA.…”
Section: Biofilmsmentioning
confidence: 99%
“…In addition to antibiotic tolerance, biofilms often represent a reservoir of genetic diversity by promoting genetic exchange between different subpopulations. Several studies have documented the increased dissemination of antibiotic resistance genes in biofilms through horizontal gene transfer, integrative conjugative elements, and natural transformation (102)(103)(104). Additionally, bacterial cells within biofilms undergo several stressful conditions, including major nutrient starvation, which could increase the mutation frequency and the emergence of antibiotic-resistant mutant strains (8,69,105,106).…”
Section: Immune Evasion and Treatment Failure Studies Of H Pylori Bimentioning
confidence: 99%
“…The analysis of “transformability” and “donatability” between Aeromonas strains showed that transformation of groups was constrained to phylogroups (Huddleston et al, 2013), consistent with some population studies that have highlighted HGT between close relatives in the genus Aeromonas (Silver et al, 2011; Roger et al, 2012b). The high concentration of extracellular DNA within a biofilm may facilitate the transformation of Aeromonas , as in other bacteria capable of natural transformation (Merod and Wuertz, 2014). …”
Section: Biofilm Formation In Aeromonasmentioning
confidence: 99%